English as a Solely Instructional Medium: Its Effectiveness on Studentsâ€™ Responses and English Proficiency - Habibi, Akhmad; Sofwan, Muhammad (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2017)
This research examined the effectiveness of English as the solely instructional medium in one informal educational institution. In the first English class, an English-only rule was strictly ruled whereas in the second English class, the use of Bahasa Jambi as the studentsâ€™ local language was permitted. The research is appropriately undertaken as a mix method research with quantitative and qualitative approach. The site of the research is an established informal English institution in Indonesia. The authors used three kinds of instruments in collecting the data; questionnaires, tests (pre-test and post-test), and interviews. Participants of the research are the students of intermediate classes of an informal education institution in Jambi. The results show that 1) the students of the first class have stronger preferences to learn English than the students of the second class 2) the studentsâ€™ English proficiency improvement of the first English class â€œunder the strict rule of the use of Englishâ€ is slightly higher than that of the second class â€œthe local language permittedâ€. Suggestions and recommendations are offered for the betterment of English teaching and learning in Indonesia.